2021
DOI: 10.1088/1755-1315/915/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Green human resource management policies and practices in Ukraine

Abstract: The main purpose of the study is to assess the development and implementation of GHRM policies and identify prospects for the dissemination of GHRM practices in Ukraine. The results of the survey confirmed the working hypotheses: the practice of developing GHRM policies in Ukraine has not become widespread and there are no effective mechanisms for implementing GHRM policies. The research showed the average level of respondents’ assessment of their awareness of GHRM practices. The study confirmed a lack of effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some research [15] showed that despite informedness, GHRM practices are still not widespread. The study by Tsymbaliuk, Vasylyk and Stoliaruk [16] proved an absence of efficient instruments for GHRM practices introduction. The research showed that HR managers have medium awareness of GHRM practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research [15] showed that despite informedness, GHRM practices are still not widespread. The study by Tsymbaliuk, Vasylyk and Stoliaruk [16] proved an absence of efficient instruments for GHRM practices introduction. The research showed that HR managers have medium awareness of GHRM practices.…”
Section: Literature Reviewmentioning
confidence: 99%